(untitled) (Fiep Bulletin - online, 2013)
This study has as objective delineates the swimming trainers’ characteristics in the city of Manaus. The sample was composed by 20 trainers. An inquiry was applied under the questionnaire form. The treatment released to the obtained data felt through descriptive analysis (average, standard deviation, frequency and percentage). The main results appear for a sample with trainer’s practical experience, that assists a great amount of students and categories for swimming class.